Physical activity self-efficacy assessment scale for seniors - Kaupužs, Aivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Physical activity (PA) self-efficacy is one of the most important psychological factors that influence older person’s health related behaviour. This study was designed to develop an appropriate instrument and examine the psychometric properties of the Physical Activity Self-efficacy Assessment Scale for seniors (PASAS). The scale development process included identifying the PA self-efficacy concept by literature reviewing, generating the items from semi-structured interviews and testing of validity and reliability. The study was carried out for testing of PASAS. The research samples consisted of 359 respondents 60-75 years old. The PASAS is a 14-item, 5-point Likert Scale. It comprises of 4 dimensions, namely, internal motivation, lack of support, health limitations and lack of recourses. The PASAS demonstrates an acceptable content validity index and construct validity (Cronbach's alpha 0.966). The criterion-related validity of PASAS was verified by a significant positive correlation (ρ = 0.47 -0.741, p < 0.01) between the developed scale items and the scores of IPAQ. The scale developed in this study can be used as research tools to measure PA selfefficacy of seniors.